The Effect of Market Structure on Sales of Coal Companies Listed on the Indonesia Stock Exchange (IDX) for the Period 2018 - 2022 - Said Nur Octavianto; Amin Pujiati; Sucihatiningsih Dian Wisika Prajanti (Universitas Muhammadiyah Ponorogo, 2024)
The limited product diversification of the Indonesian coal mining industry underscores the imperative for the formulation of strategic business plans to navigate the intensifying market competition. This study aims to examine the market structure, the factors influencing sales, and the impact of market structure on the sales performance of coal mining companies in Indonesia. This study employs a quantitative method and utilizes a range of analytical techniques, including CR4, HHI, MES, CLR, PCM, and multiple linear regression. The CR4 and HHI analysis revealed that the market structure of coal mining companies in Indonesia is classified as a highly concentrated tight oligopoly. The MES analysis yielded the conclusion that new companies in the sector face significant barriers to market entry. The findings of the CLR analysis, which indicates that the coal mining sector is a capital-intensive industry, suggest that equity and capital factors are the primary contributors to the challenges faced by new companies attempting to enter the market. The results of the multiple linear regression analysis indicate that equity factors and production volume have a positive and significant effect on company sales. This finding is corroborated by the PCM analysis, which suggests that companies with low market share tend to set higher margins to obtain greater profits. Increasing investment levels may serve as a viable business strategy, particularly when supported by government policies aimed at fostering a secure and stable investment environment to enhance company equity and capital.